KEARIFAN BUDAYA LOKAL DALAM PENGUTAN TRADISI MALEMANG DI TENGAH MASYARAKAT MODERNISASI DI SUNGAI KERUH MUSI BANYUASIN SUMATERA SELATAN - Dendi Sutarto (JURNAL DIMENSI, 2016)
This research aim at explaining to the Malemang tradition is one of the local cultural heritage of the archipelago very unique living today is Malemang tradition is a traditional community unique in the Sungai Keruh district Musi Banyuasin South Sumatra, this tradition is characterized by burning lemang morning by every population in the Kertayu village. This tradition originated from local communities for resisting disaster when the Dutch colonial era outbreaks of a disease so the tradition of resisting disaster dimension mystic is done with a series of indigenous tradition that connects the tradition Malemang, thanksgiving after the harvest the tomb of Puyang Burung Jauh and the concept of salvation, as well as religious and cultural acculturation locally very strong value system of solidarity, social cohesion, harmony, peace, and social empathy which became part of the social system culture, norms, and religion. But the times entered into a cultural struggle modernization occurred between local culture and traditions of modernization that tends to undermine the foundations of the social and cultural systems has been the pattern of action and community tradition over the years. In this study using the methodology of qualitative descriptive with approach of sociology of cultural assisted to the theory of functionalism strukturalime and social change as analysis the dynamics of the struggle between the cultural wisdom, Malemang traditions particularly in strengthening the existence in society modernization. This study resulted in that the cultural influence of modernization is very rational, capitalism, hedonism, consumerism and the stream of Western culture to Indonesia have an impact on the destruction of the foundations of the system of culture, norms, tradition so that changes in behavior patterns of society from the value of local knowledge as a social system culture that gives directions foothold in the act. Additionally began abandoning the old culture that are considered irrelevant to the modernity of the times, to address the issue of indigenous peoples should have as a cultural mechanisms to strengthen local wisdom.